FOREIGN LANGUAGE SPEAKING ANXIETY ON THE 6TH SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT - Nadzly W. Didipu; Noldy Pelenkahu; Ignatius Tuerah (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
The aim of this research is to discover the existence, the average level, and the most common type of foreign language speaking anxiety on college students. The approach of this research is quantitative. The research is conducted at the English Education Department of Universitas Negeri Manado. The population of the respondents of this research is the 6th semester students of the English Education Department of Universitas Negeri Manado. The sample consists of 20 respondents of the 6th semester students chosen using the random sampling process. The research instrument that the writers use in this study is the Foreign Language Speaking Anxiety Scale (FLSAS). The finding of this research shows that all of the respondents have experienced symptoms of speaking anxiety and have an average level of 90,3 for speaking anxiety. It is also found that the cause for foreign language speaking anxiety on most of the students is test anxiety. The result of the research suggests that the 6th semester students of the English Education Department of Universitas Negeri Manado have speaking anxiety with an average level of Moderate, and the most common type of speaking anxiety was Test Anxiety.